Meta Analisis Pengaruh Bahan Ajar Terintegrasi Model Problem Based Learning terhadap Kemampuan Pemecahan Masalah Siswa pada Pembelajaran Fisika - Asrizal; Fatni Mufit; Riza Azriyanti; Utari Prisma Dewi; Nuhamdin Putra (Postgraduate, University of Mataram, 2023)
The purpose of this research is to combine, analyze, and conclude previous studies in order to obtain accurate results regarding the effect of integrated teaching materials using the Problem Based Learning (PBL) model on students' problem solving abilities in terms of the types of teaching materials, grade levels, and subject matter. The research method used is meta-analysis by reviewing 28 articles from national and international journals. The research results obtained included: overall the mean effect size of the PBL model integrated teaching materials on students' problem solving abilities was 0.858 which was in the high category. In terms of Teaching Materials, the largest mean effect size is 2.372 with the high category belonging to the E-module. Based on the class level, the largest mean effect size is owned by class XI, which is 0.990, which is in the high category. Based on the material unit, rotational dynamics has the largest mean effect size value of 2.522 which is included in the high category. From the results of this study, it can be concluded that in general teaching materials that are integrated with the PBL model can improve students' problem-solving abilities in learning physics. If viewed from the moderator variable, it can be concluded: First, the most effective teaching material is the e-module. Secondly, it is most effectively applied to class XI. Third, it is most effectively applied to rotational dynamics material